Fenomena Pernikahan Sedarah Perspektif Psikologis: Tinjauan Dari Kacamata Islam - Janah, Miftahul; Yunita, Yunita; Arifi, Ahmad (Hadara : Journal of Da'wah and Islamic Civilization, 2025)
This study aims to analyze Inbreeding from a Psychological perspective and a Review from an Islamic Perspective. This research uses a research method, namely a qualitative approach with library research with data sources based on literature studies. Sources used in this research are books and journals, and other references. The results of this study indicate that in blood marriage, namely marriage between a woman and a man who still has a very close blood relationship. Allah SWT forbids marrying women with whom there is a mahram relationship, both because of lineage, and breastfeeding. The prohibition is permanent, until whenever and in any situation. The novelty of this research in inbreeding has a negative impact on mental health and family relationships and increases the risk of genetic disorders that can lead to a decrease in the quality of the resulting offspring. The implications of this study can serve as a reference for policy makers, mental health practitioners and the community to address the phenomenon of inbreeding.